2007
DOI: 10.3354/meps339259
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering ability of young-of-the-year bluefish Pomatomus saltatrix: effect of ration and cohort of origin on survival

Abstract: Bluefish Pomatomus saltatrix have experienced declines in recruitment and adult abundance along the US East Coast since the mid-1980s. At the onset of winter, young-of-the-year (YOY) bluefish exhibit a multimodal size distribution including larger, spring-spawned fish (spring cohort) and smaller, summer-spawned fish (summer cohort). Declines in the adult stock appear to coincide with declines in recruitment success of the summer cohort. We investigated the hypothesis that poor recruitment success of the summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The unusual energy depletion patterns observed in our data are not likely to be an artifact of sampling different portions of the population each month, because similar energy depletion patterns were observed in a laboratory experiment when fish were fed (Slater et al 2007). Slater et al (2007) determined that while larger bluefish started the winter with more energy reserves, by early spring there was no difference in energy reserves between cohorts when food was provided.…”
Section: Seasonal Energy and Feeding Dynamicssupporting
confidence: 77%
See 3 more Smart Citations
“…The unusual energy depletion patterns observed in our data are not likely to be an artifact of sampling different portions of the population each month, because similar energy depletion patterns were observed in a laboratory experiment when fish were fed (Slater et al 2007). Slater et al (2007) determined that while larger bluefish started the winter with more energy reserves, by early spring there was no difference in energy reserves between cohorts when food was provided.…”
Section: Seasonal Energy and Feeding Dynamicssupporting
confidence: 77%
“…This may be due to increasing tolerance of acute cold stress with decreasing length. Slater et al (2007) held YOY bluefish in outdoor tanks at ambient temperatures during the winter and found Cohort 2 to be more tolerant of acute cold stress mortality than Cohort 1. Increasing cold tolerance with decreasing length has also been shown for Atlantic croaker (Lankford & Targett 2001).…”
Section: Temporal Abundance and Cohort Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Also, due to the lack of previously published studies that report summer lipid values for age-0 bluefish, we were unable to compare the cohort-specific C:N lipid proxy patterns that we observed to values from the same month(s) from other regions or years. Still, it is worth noting recent work by Slater et al (2007) and Morley et al (2007) that found that spring and summer cohorts of age-0 bluefish manifested different energy allocation strategies by fall; members of the spring-spawned cohort entered the October-November overwintering period with higher lipid reserves than summerspawned fish that presumably shunted more energy into somatic growth. We observed the opposite pattern, i.e.…”
Section: Conditionmentioning
confidence: 99%